Improving Science Conceptual Understanding and Science Process Skills in Elementary School using Predict-Observe-Explain Learning Model - Fiteriani, Ida; Mulyani, Laras Dwi; Sa’idy, Sa’idy (Jurnal Pendidikan MIPA, 2023)
This study aims to determine the effect of the Predict-Observe-Explain (POE) model as an alternative learning to improve students' understanding of science concepts and process skills. All experimental designs with the Non-Equivalent Control Group Design were applied to this study. Population were all fourth-grade students at MI Nurul Islam, South Lampung. The sampling technique used non-probability sampling, with class IV A as the experimental class and class IV B as the control class. The instrument for understanding the science concept was description test and SPS assessment with a practicum observation sheet. Statistical data processing techniques were carried out descriptively and inferentially with hypothesis testing using multivariate of variance (MANOVA) with a significance level of 5%. The results showed that the average value of the experimental class was higher than that of the control class. Likewise, the results of hypothesis testing show that there is an increase in conceptual understanding and science process skills in the experimental class compared to the control class. It can be concluded that the POE learning model can be used as an alternative to improve students' understanding of science science concepts and process skills in elementary schools. Keywords: POE learning model, conceptual understanding, and science process skills.DOI: http://dx.doi.org/10.23960/jpmipa/v24i1.pp225-234